2009
DOI: 10.2147/vhrm.s5745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between automated and manual measurements of carotid intima-media thickness in clinical practice

Abstract: Background and aim: The measurement of carotid intima-media thickness (cIMT) has been used as a marker of arterial wall disease. Manual measurements have been performed in most epidemiological studies, but, due to the introduction of new technologies, automated software has been increasingly used. This study aimed to compare manual versus automated cIMT measurements in common carotid (CC), bifurcation (BIF), and internal carotid (IC). Methods: Automated and manual cIMT measurements were performed online in 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In adults, multiple studies have shown that automatic measurements usually have better reproducibility and lower variability compared to manual measurements, as it is illustrated in our study with a low coefficient of variation (3.93%) for the semi-automatic B-mode technique. 28,29 Dogan et al 30 found a poor correlation between manual and automated techniques. In fact, the precision of a manual system on a radiological screen for one pixel is of .2 mm, therefore, for a 10 mm segment, accuracy is of 9%.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, multiple studies have shown that automatic measurements usually have better reproducibility and lower variability compared to manual measurements, as it is illustrated in our study with a low coefficient of variation (3.93%) for the semi-automatic B-mode technique. 28,29 Dogan et al 30 found a poor correlation between manual and automated techniques. In fact, the precision of a manual system on a radiological screen for one pixel is of .2 mm, therefore, for a 10 mm segment, accuracy is of 9%.…”
Section: Discussionmentioning
confidence: 99%